Scorpion diversity of the Central Andes in Argentina - Fernández Campón, María Florencia (2014)
Mountain habitats host a large number of endemic species, which are vulnerable to climate change. We studied scorpion communities of the Central Andes in Argentina at 17 sites located in Andean and extra-Andean areas between 900 and 3400 m elevation. Using pitfall traps, we collected 254 individuals from seven species, all from the Bothriuridae family. Although we expected a decrease in richness towards the high altitude sites, we did not find a clear pattern. In turn, the lowest site was the most diverse and rich; other sites had similar richness values regardless of altitude. High-altitude sites were characterized by the presence of Orobothriurus Maury 1975 species. Orobothriurus alticola (Pocock 1899) has been found exclusively on Andean sites located above 3200 m, and O. grismadoi Ojanguren-Affilastro et al. 2009 has only been found at extra-Andean sites on Cerro Nevado. Community composition showed an association with altitude, with some species exclusive to high altitude sites and others only found at lower sites. Because of the ecological importance of scorpions in arid environments, this study provides base information that may help design conservation actions for these habitats. In particular, the presence of high-altitude specialists like Orobothriurus species seems relevant, since they may be used as bioindicator species.